Stability of blended palm oils during potato frying - Azimah, R.; Azrina, A.; Khoo, H. E. (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2017)
The aim of this study was to determine hydrolytic stability [acid value (AV)] and oxidative stability [peroxide value (PV) and conjugated dienes (CD)] of selected blended oils during potato frying. The blended oils were prepared by blending palm oil with corn oil (POCO), sesame oil (POSO) and rice bran oil (PORBO). Blended vegetable oils were prepared in a ratio of 1 to 1 (v/v) and tested for 0, 10 and 20 times after frying potato. AV and PV were determined by titration method, while CD was determined using the spectrophotometric method. Increasing frequency of oil frying contributed to increased level of AV in all blended oils. PVs were increased in all samples, with most noticeable increment observed in POSO, followed by PORBO and POCO. CD levels of the blended oils were also increased after 20 times of potato frying compared with the unused oil and after 10 times of frying. POCO was the most stable oil in terms of hydrolytic and oxidative stabilities. It is most suitable for deep-fat frying of potato chips and industrial application.